MOTIF DAN KEPUASAN MENONTON TAYANGAN PROGRAM MUSIK BREAKOUT NET TV PADA SISWA SEKOLAH MUSIK YAMAHA PEKANBARU - Gustiawansyah, Muhammad Haikal; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The progress of mass media, especially the media today is increasing rapidly, where television broadcasting has enabled the wider community to quickly and easily know the various changes that occur in various world juveniles. In general, people love the impressions or music programs (entertainment news). Breakout Net tv is a news show about favorite music with different presentation characteristics. In the theory of usage and gratification, audiences basically use mass media based on certain motives, in which the media is needed to meet the needs of the audience which is called effective medium. The aim of this research is Breakout Music Net Tv on student satisfaction Music School Yamaha Pekanbaru.The method used in this research is quantitative explanatory. Data was collected using a questionnaire. research location in Yamaha Pekanbaru music school. the population is the School of Yamaha Music students as many as 82 respondents. The analysis test used in this study is path analysis and to process questionnaire data, it is done using the SPSS for Windows version 23 program.the results obtained from this study using simple linear regression analysis concluded that this study in accordance with the theory used is the uses and gratification theory and this study also showed that the value of satisfaction watching Breakout Net Tv shows exceeded expectations of the value of the Motive watching Breakout Net Tv shows . The motive of watching the Influential Net Tv show was 12.6% on the satisfaction of watching Breakout Net Tv shows obtained by Students of Yamaha Pekanbaru Music School. The influence is included in the weak category and the remaining 87.4% is influenced by other variables not examined in this study.Keywords: Motive, Intensity, Satisfaction, Manga, Media Usage